2010
DOI: 10.1021/bi100605e
|View full text |Cite
|
Sign up to set email alerts
|

Using Fluorine Nuclear Magnetic Resonance To Probe the Interaction of Membrane-Active Peptides with the Lipid Bilayer

Abstract: A variety of biologically active peptides exert their function through direct interactions with the lipid membrane of the cell. These surface interactions are generally transient and highly dynamic, making them hard to study. Here we have examined the feasibility of using solution phase (19)F nuclear magnetic resonance (NMR) to study peptide-membrane interactions. Using the antimicrobial peptide MSI-78 as a model system, we demonstrate that peptide binding to either small unilamellar vesicles (SUVs) or bicelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 35 publications
(48 reference statements)
4
44
0
Order By: Relevance
“…In spite of evidence for some exchange broadening of the Trp187 side chain H ε 1 resonance compared to the analogous resonances for other tryptophan residues in NS1A ED (Figure 1C), this 1 H resonance features a much narrower chemical shift dispersion and a different local environment, rendering it less sensitive to conformational exchange phenomena compared to the fluorinated tryptophan strategy. In the context of the broader 19 F protein NMR literature, these dynamical results on the NS1A ED dimer interface constitute a novel application of 19 F NMR relaxation to directly probe slow motion dynamics within a protein:protein interface The NMR properties of 19 F have, have been exploited recently to illuminate slow motion conformational dynamic processes in other types of interactions including protein-ligand interactions (Ahmed et al, 2007), peptide-bicelleinteractions (Buer et al, 2010), changes in dynamics accompanying protein complex formation (Acchione et al, 2012), and the thermodynamic and kinetic aspects of domain swapping (Liu et al, 2012). In addition, 19 F CPMG relaxation approaches were recently employed to characterize the conformational exchange behavior of fluorinated Phe residues in the thermal folding intermediate of calmodulin (Kitevski-Leblanc et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of evidence for some exchange broadening of the Trp187 side chain H ε 1 resonance compared to the analogous resonances for other tryptophan residues in NS1A ED (Figure 1C), this 1 H resonance features a much narrower chemical shift dispersion and a different local environment, rendering it less sensitive to conformational exchange phenomena compared to the fluorinated tryptophan strategy. In the context of the broader 19 F protein NMR literature, these dynamical results on the NS1A ED dimer interface constitute a novel application of 19 F NMR relaxation to directly probe slow motion dynamics within a protein:protein interface The NMR properties of 19 F have, have been exploited recently to illuminate slow motion conformational dynamic processes in other types of interactions including protein-ligand interactions (Ahmed et al, 2007), peptide-bicelleinteractions (Buer et al, 2010), changes in dynamics accompanying protein complex formation (Acchione et al, 2012), and the thermodynamic and kinetic aspects of domain swapping (Liu et al, 2012). In addition, 19 F CPMG relaxation approaches were recently employed to characterize the conformational exchange behavior of fluorinated Phe residues in the thermal folding intermediate of calmodulin (Kitevski-Leblanc et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MSI-78 adopts an α-helical structure on association with the cell membrane and a random coil structure in aqueous buffer solutions. 27,28 Its short sequence and α-helical structure make it a good choice for structural characterization.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of fluorinated amino acids into proteins has attracted particular interest, because although essentially absent from biology, fluorine has proved a remarkably useful element to probe the workings of biological molecules. For example, fluorinated substrates have been extensively used to investigate enzyme mechanisms, and 19 F NMR has proved a valuable tool for studying structure, dynamics, and interactions of fluorine-labeled proteins, peptides, lipids, and nucleic acids (4)(5)(6)(7)(8)(9). Fluorinated molecules also have important medical applications, exemplified by 20% of all pharmaceuticals containing fluorine, which improves pharmacokinetic properties (10).…”
mentioning
confidence: 99%